2021
DOI: 10.1200/go.20.00079
|View full text |Cite
|
Sign up to set email alerts
|

Cervix Cancer in Sub-Saharan Africa: An Assessment of Cervical Cancer Management

Abstract: PURPOSE Underdeveloped nations carry the burden of most cervical cancer, yet access to adequate treatment can be challenging. This report assesses the current management of cervical cancer in sub-Saharan Africa to better understand the needs of underdeveloped nations in managing cervical cancer. METHODS A pre- and postsurvey was sent to all centers participating in the Cervical Cancer Research Network's 4th annual symposium. The pre- and postsurvey evaluated human papillomavirus and HIV screening, resources av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…In South Africa, it is the most common cancer amongst the black female population, with an agestandardized incidence rate of 28.25 per 100,000 and a lifetime risk of 1 in 33 [2]. Treatment of cervical cancer may include surgery, radiotherapy, chemotherapy, or a combination of modalities based on International Federation of Gynecology and Obstetrics (FIGO) stage [3]. Concurrent chemoradiotherapy using weekly cisplatin as the chemotherapeutic agent is the standard of care as an outpatient therapy for locally advanced cervical cancer (LACC), commonly diagnosed in our setting [4].…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, it is the most common cancer amongst the black female population, with an agestandardized incidence rate of 28.25 per 100,000 and a lifetime risk of 1 in 33 [2]. Treatment of cervical cancer may include surgery, radiotherapy, chemotherapy, or a combination of modalities based on International Federation of Gynecology and Obstetrics (FIGO) stage [3]. Concurrent chemoradiotherapy using weekly cisplatin as the chemotherapeutic agent is the standard of care as an outpatient therapy for locally advanced cervical cancer (LACC), commonly diagnosed in our setting [4].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in sub-Saharan Africa ultrasound (78%), computed tomography (CT) (47%) and intravenous pyelogram (5%) were used to evaluate for hydronephrosis. Most centres used CT (73%), followed by ultrasound (52%), MRI (26%) and positron emission tomography-computed tomography (PET-CT) (16%) to assess for metastatic lymph [5]. CT scanning, which is a sufficiently accurate tool for assessing lymph node involvement and distant metastasis, is more commonly used in LMICs.…”
Section: Imaging Modalities For Stagingmentioning
confidence: 99%
“…In the East African countries, it ranges between 25 and 40% of all cancers. Africa has the highest age-standardised cervical cancer incidence and mortality rates in the world [5]. Within the continent, there is significant variation in incidence and death from cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, assessment of tumor sensitivity to radiotherapy is key to selecting treatment Gynecological examination less clinically useful than MRI because it is subjective and does not precisely assess the necrosis and residual status of the tumor. MRI has the advantages such as zero radiation and easy operation, which can objectively evaluate the progression and regression of lesions, and in particular, T 1 WI-enhanced scan can show the ischemic and necrotic areas within the tumor at an early stage, which is beneficial for predicting the effect of radiotherapy [19][20][21]. e study found that before treatment, MRI finding of cervical lesion was irregular soft tissue mass, T 2 WI appeared mixed signal intensity or hyperintensity, with necrotic tissue and fat suppression being hyperintensity; after treatment, lesions shrunk, originally abnormal signals in 5 patients disappeared, and after T 1 WI enhancement, mild enhancement could be seen in 41 patients and no enhancement in 4 patients, which demonstrated that MRI could provide more valuable information of efficacy assessment for the clinical physicians.…”
Section: Discussionmentioning
confidence: 99%